2015
DOI: 10.1007/s11033-015-3855-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induced altered expression of heat shock protein genes (Hsc71, Hsp90α and Hsp10) in Indian Catfish, Clarias batrachus (Linnaeus, 1758) under oxidative stress

Abstract: Heat shock proteins (Hsps) are typically associated with stress response and tolerance. The Indian catfish, Clarias batrachus, is a freshwater air-breathing hypoxia tolerant teleost and is potentially important catfish species for aquaculture and for its economic value as food. The present study aimed at determining the transcriptional response of three Hsps, CbHsc71, CbHsp90α and CbHsp10 in hypoxia tolerant Indian catfish, C. batrachus, under experimental and natural hypoxia. The expression profile of above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…It is interesting that the heat shock cognate 70–2 ( hsc70 ) was enriched in 5 KEGG pathways (corrected p-value < 0.05): influenza a (ko05164); legionellosis (ko05134); estrogen signaling pathway (ko04915); measles (ko05162); antigen processing and presentation (ko04612), indicate that hsc70 plays a comprehensive role in the acute thermal stress response, a result that has been shown in different species 4 , 37 , 38 . Similar to the present results, other studies have reported that hsc71 is up-regulated after hypoxia stress 39 . Interleukin 1 beta (IL-1β) is an evolutionarily conserved molecule originally identified in the immune system, and it plays a critical role in the activation of immune cells 40 .…”
Section: Discussionsupporting
confidence: 93%
“…It is interesting that the heat shock cognate 70–2 ( hsc70 ) was enriched in 5 KEGG pathways (corrected p-value < 0.05): influenza a (ko05164); legionellosis (ko05134); estrogen signaling pathway (ko04915); measles (ko05162); antigen processing and presentation (ko04612), indicate that hsc70 plays a comprehensive role in the acute thermal stress response, a result that has been shown in different species 4 , 37 , 38 . Similar to the present results, other studies have reported that hsc71 is up-regulated after hypoxia stress 39 . Interleukin 1 beta (IL-1β) is an evolutionarily conserved molecule originally identified in the immune system, and it plays a critical role in the activation of immune cells 40 .…”
Section: Discussionsupporting
confidence: 93%
“…mytiligera from its substrate may also account for a different pattern of protein expression. The list of significant proteins nonetheless includes potential biomarkers for various stressors such as actin [44], 14-3-3 proteins [37], and Hsc71 [45].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, during the night, biogeochemical conditions at the base of the mat are typically hypoxic or anoxic with high levels of sulfide and low pH (reviewed in Sato et al 2016). It is well known that usually both hyperoxia and hypoxia, as well as the exposition to sulfide, may lead to the upregulation of the antioxidant systems HO-1 and MnSOD as well as that of Hsps (Lee et al 1997;Yamashita et al 1997;Carraway et al 2000;Garrido et al 2001;Richier et al 2003;Calvert et al 2009;Mohindra et al 2015). Moreover, sulfide is toxic to most eukaryotes, inhibiting electron transport in aerobic respiration, leading to apoptosis and tissue necrosis, and increasing the cellular oxidative stress (Vismann 1991).…”
Section: Discussionmentioning
confidence: 99%